Some Feedback on the Formation of the Anthropogenic Landscape in Ancient Ferghana - Z. R. Kuchkarova (Researchparks Publishing, 2021)
this article covers the analysis of the formation processes of the first artificial irrigation-based farming in ancient Fergana, as well as the establishment of the first settlements.